Differentiation and Grouping Practices as a Response to Heterogeneity – Teachers’ Implementation of Inclusive Teaching Approaches in Regular, Inclusive and Special Classrooms - Lindner, Katharina-Theresa; Nusser, Lena; Gehrer, Karin; Schwab, Susanne (Frontiers in Psychology, 2021)
Addressing students’ individual needs is a crucial component of inclusive teaching. However, empirical evidence comparing practices such as differentiation and grouping strategies within inclusive, regular and special classes is still lacking. The present study contrasts these settings using data from the German National Educational Panel Study (NEPS). Data from 1034 German class teachers (755 regular, 89 inclusive, 190 special teachers) teaching the subject German in secondary school (grade 5 to grade 8) were used. Results show the highest use of differentiation in special school classes. Teachers’ use the majority of the grouping practices is similar comparing the three educational settings. Class size and the number of students with migration background were predictors for teachers’ use of differentiation, whereas profiles/patterns of grouping strategies were predicted by students’ gender and teachers’ experience.